Queue System Analysis Happy World Consumers Using Single Chanel Multi-Phase Queue Model - Hertati Ervinna Siahaan; Jonson Manurung (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
Happy World is a playground for children or adults on JL. Serdang Baru, Deli Mas Plaza Complex 3rd Floor which has customers or consumers who visit to want to play. The problem with Happy World is that it doesn't have the technology yet, in terms of structuring or setting the cashier's service time, which still uses a manual by taking a queue number. These problems resulted in the accumulation of customers at the cashier and did not comply with health protocols. Therefore the company needs fast service to serve all its customers without compromising the quality of the service. That builds customer confidence in the cashier's service and creates a system to help make the queue more neat and orderly so that the services provided can also satisfy the customer, namely the Queue System. From the test results, the performance obtained in the payment queuing system needs at the cashier (server) where the average service time spent at the cashier and efficient service time, the company exceeds the service time limit that has been set, which is 10 minutes to reduce the level of service delivery. density, the company will repair the system.